Overproduction of a penicillin-binding protein is not the only mechanism of penicillin resistance in Enterococcus faecium. - Klare, I (1992)
In 1989 and 1990, a large number of ampicillin-resistant strains of Enterococcus faecium were isolated from infected patients treated at intensive care units in Berlin, Germany. Twenty-five clinical isolates, including five different biotypes as classified by acid production from various sugars and a wide range of susceptibilities to ampicillin (MICs between 0.5 and 128 micrograms/ml), were selected for a detailed analysis of penicillin-binding proteins (PBPs). All strains contained a slowly reacting PBP with low penicillin affinity known to be present in enterococci. Overproduction of this PBP relative to susceptible isolates was noted, especially in all strains for which the MIC of ampicillin was 8 micrograms/ml, to a lesser degree in the more resistant strains, but not at all in the three highly resistant isolates for which the MIC was 128 micrograms/ml. In these three strains, this PBP appears to have a reduced affinity for beta-lactams. The results suggest that overproduction of PBP 6 correlates only with intermediate resistance levels and that higher resistance is mediated by yet another, still unknown mechanism, probably including reduction of beta-lactam affinity in one or more PBPs.